O esboço de gráficos de polinômios de 2º e 3º graus usando derivadas - Biano, Adão de Aguiar (2015)
In this work is submitted a differentiated of proposal to draft graphics of polynomials of second and third degrees, where we suggest the use of derivative to accomplish this task. For this we developed some basic concepts of calculus in early labor, such as limits notions, the problem of the tangent line, derivative’s definition and how to derive polynomial functions. In the following other previous concepts calculus that will give us the necessary support to reach the outline of graphics polynomials of second and third degrees, and finally leave at the end of work a suggestion for the high school teachers how to apply what was proposed in the classroom so that students have a significant learning.